Solubility of Tar Model Compounds in Various Solvents for Tar Removal in a Dual Fluidized Bed Biomass Gasification Process. Issue 1 (June 2021) - Tonpakdee, Pimnara; Hongrapipat, Janjira; Siriwongrungson, Vilailuck; Pang, Shusheng; Rauch, Reinhard; Messner, Michael
Abstract: Production of high quality product gas via biomass steam gasification is a promising technology. However, impurities in the product gas, namely tars, cause problems in the downstream gas processing operations and thus they need to be removed efficiently. Oil scrubbing is an effective solution for tar removal due to its non-polar characteristic which is similar to tar nature. In this research, solubility values of five simulated tar compounds were experimentally investigated for selecting the new scrubbing solvent. The simulated tar compounds investigated represent those found in the dual fluidized bed steam gasification of wood biomass, which are: naphthalene, biphenyl, anthracene, fluoranthene, and pyrene. The scrubbing solvents tested in this research are classified into biodiesels, vegetable oils, and diesel. Biodiesel used are rapeseed methyl ester (RME) and 2 different palm methyl esters (denoted as PME1 and PME2). Vegetable oils are sunflower oil, refined palm oil, Thai rice bran oil, and crude palm oil. All of the solubility tests were performed in the laboratory-scale test-rig at 30, 50, 70, and 80°C. Biodiesels are found to be the effective solvent in dissolving the tar compounds. PME1 shows the similar tar removal performance to RME but is more readily available; therefore, PME1 is chosen to be used as a scrubbing solvent at the Thailand 1 MWel prototype DFB gasifier at Nong Bua district in Nakhon Sawan province, Thailand.